The economics of abortion: Costs, impacts, values, benefits, and stigma - Ernestina Coast; Samantha R. Lattof; Yana Rodgers; Brittany Moore; Cheri Poss; Joe Strong (London School of Economics and Political Science (LSE), Department of International Development, 2022)
Objective: To systematically search for and synthesize the social science literature on the consequences of abortion-related care, abortion policies, and abortion stigma on economic costs, benefits, impacts, and values at the micro- (i.e., abortion seekers and their households), meso- (i.e., communities and health systems), and macro- (i.e., societies and nation states) levels. Methods: We conduct a scoping review using the PRISMA extension for Scoping Reviews (PRISMA-ScR) tool. Studies reporting on qualitative and/or quantitative data from any world region are considered. For inclusion, studies must examine one of the following economic outcomes at the micro- , meso-, and/or macro-levels: costs, benefits, impacts, and/or value of abortion-related care or abortion policies. Results: Our searches yielded 19,653 unique items, of which 365 items were included in our synthesis. The economic levels are operationalized as follows: at the micro-level we examine individual decision making, at the meso-level we consider the impact on abortion services and medical systems in context, and at the macro the impact of access to abortion services on broader indicators (e.g., women's educational attainment). At the micro-economic level, results indicate that economic costs and consequences play an important role in women's trajectories to abortionrelated care. However, the types of costs that are studied are often unclear and tend to focus narrowly on costs to and at health facilities. Our evidence suggests that a much broader range of economic costs, impacts and values are likely to be important in a wide range of contexts. At the meso-economic level, we find that adapting to changes in laws and policies is costly for health facilities, and that financial savings can be realized while maintaining or even improving quality of abortion care services. At the macro-economic level, the evidence shows that post-abortion care services are expensive and can constitute a substantial portion of health budgets. Public sector coverage of abortion costs is sparse, and women bear most of the financial costs. Conclusions: This scoping review has uncovered a wealth of information about the economic costs, impacts, value, and benefits of abortion services and policies. The review also points to knowledge gaps, such as the ways in which women perceive the intersections between costs and quality of care, safety, and risk. Similarly, there is a dearth of methodological variation and innovation, with an abundance of studies using costing methods and regression analysis while other tools seen elsewhere in behavioral studies (such as discrete choice experiments and randomized control trials) are underexploited. This study provides a conceptual mapping of the economics of abortion in a new way, reinforcing some findings already well known while uncovering underexplored questions and methods.
Keywords: 330; abortion services; abortion policy; health economics; scoping review; reproductive health; contraception; termination of pregnancy